BATIK TEBO DI KECAMATAN TEBO TENGAH KABUPATEN TEBO PROVINSI JAMBI (Studi Kasus di Sanggar Mursida) - Dewi, Liyan Puspita; Adriani, Adriani; Nelmira, Weni (Journal of Home Economics and Tourism, 2015)
Typical Batik Tebo yet well know neven Tebos ociety, because theproblem sare fearedlostits cultural value. This study aimed to describe about thecraft of Batik Tebo which includeforms ofmotive, the meaning containedin themotif, as well astools andmaterials for batik making techniquesin the studioMursida Tebo. The method usedin this researchis descriptive methodqualitatively.Collecting datain this studyis doneby usingthe techni ques of observation,interview sand documentation. Datareviewed andanalyzed byt he stepsof datareduction, data presentation. Data validation was donewith the extensionofobservation, increa sepersistene and triangulation.The results showed that BatikTeboconsists of 11. motif batik bambu runcing, motif batik sialang rajo, motifbatik buah manggis,motif batik rebung nyengum, motif batik serat kayu rengas,motif batik tapak kudo, motif batik bungo tanjung dan buah sawit, motif batiktapak kudo buah sawit, motif batik bungo tanjung,motif batik bungo paku danbuah sawit dan motif batik pawn(koin). Batik technique used is the technique ofbatik yestaining.Keyword : Batik Tebo, Studio Mursida, TeboCentralDistricts